Epigenetic Regulation of Interleukin 6 by Histone Acetylation in Macrophages and Its Role in Paraquat-Induced Pulmonary Fibrosis - Hu, Lingli; Yu, Yanfang; Huang, Huijie; Fan, Hanting; Hu, Li; Yin, Caiyong; Li, Kai; Fulton, David J. R.; Chen, Feng (Frontiers in Immunology, 2017)
Overexpression of IL-6 has been proposed to contribute to pulmonary fibrosis and other fibrotic diseases. However, the regulatory mechanisms as well as the role of IL-6 in fibrosis remain poorly understood. Epigenetics refers to alterations of gene expression without changes in the DNA sequence. Alternation of chromatin accessibility by histone acetylation acts as a critical epigenetic mechanism to regulate a variety of gene transcription. The goal of this study was to determine the impact of IL-6 in paraquat induced pulmonary fibrosis and to explore whether the epigenetic regulations may play a role in transcriptional regulation of IL-6. In paraquat treated lungs and macrophages, we found that the mRNA and protein expression of IL-6 was robustly increased in a time-dependent and a dose-dependent manner. Our data demonstrated that paraquat induced IL-6 expression in macrophages plays a central role in pulmonary fibrosis through enhanced epithelial to mesenchymal transition (EMT). IL-6 expression and its role to enhance paraquat induced pulmonary fibrosis were increased by HDAC inhibition and prevented by HAT inhibition. In addition, the ability of CRISPR-ON transcription activation system (CRISPR-ON) to promote transcription of IL-6 was enhanced by HAT inhibitor and blocked by HDAC inhibitor. We further showed that ChIP experiments revealed that HDAC inhibitors increase histones activation marks H3K4me3 and H3K9ac at IL-6 promoter regions. In conclusion, IL-6 functioning through EMT in paraquat induced pulmonary fibrosis was regulated dynamically by HDAC and HAT both in vitro and in vivo via epigenetically regulating chromatin accessibility.